1994
DOI: 10.1021/jm00032a015
|View full text |Cite
|
Sign up to set email alerts
|

[D-TRP32]Neuropeptide Y: A Competitive Antagonist of NPY in Rat Hypothalamus

Abstract: Neuropeptide Y (NPY) is a potent orexigenic peptide. Structure-activity studies have revealed that nearly the entire sequence of NPY is required to elicit feeding responses. Therefore, in order to develop antagonistic peptides for NPY-induced feeding, we synthesized full-length analogs of NPY, substituting D-Trp in the C-terminal receptor binding region, and screened their activity in rat hypothalamus. Although [D-Trp36]NPY and [D-Trp34]NPY inhibited isoproterenol-stimulated hypothalamic membrane adenylate cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
51
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 15 publications
0
51
0
1
Order By: Relevance
“…Neuropeptide Y and galanin are of high interest in various biological studies due to their important roles such as food intake control and cognition. Although they are abundant in the brain, 43 they have not been reported in previous neuropeptidomic studies with high confidence, probably because of its high hydrophobicity and long sequence. 44 The reliable identification of such long and hydrophobic neuropeptides using our approach assists an exploration of their roles in physiological and behavioral processes.…”
Section: ■ Discussionmentioning
confidence: 84%
“…Neuropeptide Y and galanin are of high interest in various biological studies due to their important roles such as food intake control and cognition. Although they are abundant in the brain, 43 they have not been reported in previous neuropeptidomic studies with high confidence, probably because of its high hydrophobicity and long sequence. 44 The reliable identification of such long and hydrophobic neuropeptides using our approach assists an exploration of their roles in physiological and behavioral processes.…”
Section: ■ Discussionmentioning
confidence: 84%
“…The C-terminal tetrapeptide builds a turn structure and its correct folding and orientation is of utmost importance because the affinity is only provided after stabilizing this conformation. The role of Thr32 is not clear, since replacement by Ala led to a loss of affinity by 103-fold, whereas high affinity and antagonistic properties are reported for a peptide with the exchange by D-TY (Balasubramaniam et al, 1994). Part of the amino acids of the a-helix may be involved as well as the properly orientated N-terminal segment.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been shown that both Y 1 and Y 5 receptor antagonists can inhibit NPY-induced food intake (13,14). One limitation of the agonists currently used for in vivo studies is the lack of receptor selectivity; NPY and PYY bind to the receptors Y 1 (12), but antagonism against NPY-induced increase in food intake has been observed as well (16,17 Because highly specific tools to investigate the Y 5 receptor activity are still missing, we have focused our work on the design of NPY receptor agonists with both high affinity and selectivity for the Y 5 subtype. It is well established that the C-terminal part of NPY represents the interaction site with the Y receptors and that amino acid exchange is poorly tolerated in the region 33-36 (49); therefore, we induced a conformational change within the peptide region that mediates receptor binding by introducing the ␤-turn-inducing dipeptide Ala-Aib (aminoisobutyric acid) (19) (21).…”
mentioning
confidence: 99%